2017
DOI: 10.1097/pts.0000000000000343
|View full text |Cite
|
Sign up to set email alerts
|

Learning From Incident Reporting? Analysis of Incidents Resulting in Patient Injuries in a Web-Based System in Swedish Health Care

Abstract: Objectives Incident reporting (IR) systems have the potential to improve patient safety if they enable learning from the reported risks and incidents. The aim of this study was to investigate incidents registered in an IR system in a Swedish county council. Methods The study was conducted in the County Council of Östergötland, Sweden. Data were retrieved from the IR system, which included 4755 incidents occurring in somatic care that resulted in patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
17
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 13 publications
2
17
0
Order By: Relevance
“…[7,16,28,49] However, a recent study conducted revealed that over half of the adverse drug events were significant (52.7%), with 37.1% being serious, 9% life-threatening, and 3% fatal. [28] Study results delineated that staff factors contributing to MAEs (e.g., staff not following policies and procedures [14,42] and heavy workloads [27] ) are similar to other results in the literature. This study also elucidated inadequate assessment as contributing to MAEs.…”
Section: Discussionsupporting
confidence: 75%
See 2 more Smart Citations
“…[7,16,28,49] However, a recent study conducted revealed that over half of the adverse drug events were significant (52.7%), with 37.1% being serious, 9% life-threatening, and 3% fatal. [28] Study results delineated that staff factors contributing to MAEs (e.g., staff not following policies and procedures [14,42] and heavy workloads [27] ) are similar to other results in the literature. This study also elucidated inadequate assessment as contributing to MAEs.…”
Section: Discussionsupporting
confidence: 75%
“…This study also elucidated inadequate assessment as contributing to MAEs. The second most common factor contributing to MAEs, ineffective communication, also echoes other studies that have reported miscommunication, including between healthcare providers [3,27,34,37,42] and patients and inadequate records. [3] For example, in one study, causes attributed to communication and information (errors involving misunderstanding during handovers and insufficiently explicit information/communication) represented 20% of the 448 causes.…”
Section: Discussionsupporting
confidence: 66%
See 1 more Smart Citation
“…As shown in Table 1, the incident reports provided the required information indicating good quality of the data and thus strengthening the validity of the analysis. Furthermore, data from IRSs can yield learning at the organisational and individual levels as previously suggested [19]. The main analysis focussed on the free-text section, which might capture the true value of the reports [18].…”
Section: Methodological Considerationsmentioning
confidence: 99%
“…Reporting rates are important, but they are probably inaccurate as an indicator of the safety of a hospital [18]. Instead, there is a trend towards how IRSs can result in learning at the organisational and individual levels [19]. Previous studies have used data from IRSs regarding mainly patients [18][19][20][21]; a few have focussed on HCWs, but rarely have they explored IRS data including both patient and HCW incidents.…”
Section: Introductionmentioning
confidence: 99%